Sentiment Analysis of Web Sites Related to Vaginal Mesh Use in Pelvic Reconstructive Surgery. Issue 6 (November 2019) - Hobson, Deslyn T.G.; Meriwether, Kate V.; Francis, Sean L.; Kinman, Casey L.; Stewart, J. Ryan
Abstract : Objectives: The purpose of this study was to utilize sentiment analysis to describe online opinions toward vaginal mesh. We hypothesized that sentiment in legal Web sites would be more negative than that in medical and reference Web sites. Methods: We generated a list of relevant key words related to vaginal mesh and searched Web sites using the Google search engine. Each unique uniform resource locator (URL) was sorted into 1 of 6 categories: "medical", "legal", "news/media", "patient generated", "reference", or "unrelated". Sentiment of relevant Web sites, the primary outcome, was scored on a scale of −1 to +1, and mean sentiment was compared across all categories using 1-way analysis of variance. Tukey test evaluated differences between category pairs. Result: Google searches of 464 unique key words resulted in 11, 405 URLs. Sentiment analysis was performed on 8029 relevant URLs (3472 legal, 1625 "medical", 1774 "reference", 666 "news media", 492 "patient generated"). The mean sentiment for all relevant Web sites was +0.01 ± 0.16; analysis of variance revealed significant differences between categories ( P < 0.001). Web sites categorized as "legal" and "news/media" had a slightly negative mean sentiment, whereas those categorized as "medical, " "reference, " and "patient generated" had slightly positive mean sentiments. Tukey test showed differences between all category pairs except the "medical" versus "reference" in comparison with the largest mean difference (−0.13) seen in the "legal" versus "reference" comparison. Conclusions: Web sites related to vaginal mesh have an overall mean neutral sentiment, and Web sites categorized as "medical, " "reference, " and "patient generated" have significantly higher sentiment scores than related Web sites in "legal" and "news/media" categories. Abstract : Supplemental digital content is available in the text.In regard to vaginal mesh, "medical, " "patient-generated, " and "reference" Web sites have a more positive sentiment than those categorized as "legal" or "news/media."